The Effect Of Resilience And Emotional Intelligence On Work Attachment In Financial Services Industry Employees In Medan City - Sri Hartini; Lasio Agi Jayanta Sembiring; Siska Maria Oktaviani Br Hutagaol; Calley Ang; Febe Rosuli Cuaca Simare Mare; Irma Eva Simangunsong (SEAN Institute, 2024)
This study aims to determine the influence of emotional intelligence and resilience on employee engagement in the financial services industry in Medan City. A quantitative method was employed. The study involved 111 individuals, selected using simple random sampling. The resilience scale consisted of 16 items, the emotional intelligence scale 14 items, and the employee engagement scale 15 items. Data were collected using Likert scale questionnaires administered to the subjects. Multiple linear regression analysis was used to analyze the data. Classical assumption tests, including tests for normality, heteroscedasticity, multicollinearity, and autocorrelation, were conducted before hypothesis testing. The analysis technique involved multiple regression to test the major hypothesis, the first minor hypothesis, and the second minor hypothesis. The results showed that here is a significant relationship between resilience and emotional intelligence and employee engagement, with an F-value of 63.673 greater than the F-table value (3.08) and a significance level of 0.000 less than 0.05, indicating that the major hypothesis is accepted. There is no significant relationship between resilience and employee engagement, with a t-value of -0.782 less than the t-table value (1.9821) and a significance level greater than 0.05, indicating that the first minor hypothesis is rejected. There is a significant relationship between emotional intelligence and employee engagement, with a t-value of 11.258 greater than the t-table value (1.9821) and a significance level of 0.000 less than 0.05, indicating that the second minor hypothesis is accepted.